Exploiting Beneficial Pseudomonas spp. for Cannabis Production - Balthazar, Carole; Joly, David L.; Filion, Martin (Frontiers in Microbiology, 2022)
Among the oldest domesticated crops, cannabis plants (Cannabis sativa L., marijuana and hemp) have been used to produce food, fiber and drugs for thousands of years. With the ongoing legalization of cannabis in several jurisdictions worldwide, a new high-value market is emerging for the supply of marijuana and hemp products. This creates unprecedented challenges to achieve better yields and environmental sustainability, while lowering production costs. In this review, we discuss the opportunities and challenges pertaining to the use of beneficial Pseudomonas spp. bacteria as crop inoculants to improve productivity. The prevalence and diversity of naturally occurring Pseudomonas strains within the cannabis microbiome is overviewed, followed by their potential mechanisms involved in plant growth promotion and tolerance to abiotic and biotic stresses. Emphasis is placed on specific aspects relevant for hemp and marijuana crops in various production systems. Finally, factors likely to influence inoculant efficacy are provided, along with strategies to identify promising strains, overcome commercialization bottlenecks, and design adapted formulations. This work aims at supporting the development of the cannabis industry in a sustainable way, by exploiting the many beneficial attributes of Pseudomonas spp.